Comparative Efficacy of Soft Tissue Massage and Transcutaneous Electric Nerve Stimulation in the Management of Hemiplegic Shoulder Pain (Nigerian Journal of Physiological Sciences, 2020)
BACKGROUND: Hemiplegic Shoulder pain (HSP) is a common clinical consequence of focal cerebral insult. The study investigated the comparative efficacy of Transcutaneous Electrical Nerve Stimulation (TENS) and Soft Tissue Massage (STM) in the management HSP.METHOD: A total of 50 consenting stroke patients with HSP completed the 8 weeks pretest posttest quasi-experimental study. They were assigned into either TENS or STM groups using simple random sampling. Both TENS and STM treatments were administered on subscapularis, supraspinatus and posterior deltoid muscles for 16 sessions. HSP was evaluated pre and post intervention with visual analog scale. Within and between group differences in HSP were compared using paired and unpaired t-tests respectively with SPSS version 16.0 with probability level of 0.05 to indicate level of significance.RESULTS: The age of patients in the TENS and STM groups was 56±9.26years and 57±7.51years respectively. Duration of stroke was 10±6 months and 9±4 months for TENS and STM groups respectively. There was no significant between group differences in HSP at baseline (TENS=4.76±2.17; STM=5.48±2.06; p>0.05). Within group comparison of HSP scores pre and post intervention in the TENS group indicated a significant reduction (P